Association between behavioral patterns and depression symptoms: dyadic interaction between couples - Yang, Qianhui; Gao, Xin; Tang, Ying; Gan, Hong; Wang, Baoling; Li, Mengdie; Pan, Guixia; Bao, Shuangshuang; Zhu, Peng; Shao, Shanshan; Tao, Fangbiao (Frontiers in Psychiatry, 2023)
Background Behavioral patterns are sometimes associated with depression symptoms; however, few studies have considered the intra-couple effects. This study examined the effect of a spouses’ behavioral patterns on depression symptoms within themself and in their spouse. Methods A total of 61,118 childbearing age participants (30,559 husband-wife dyads) were surveyed. The depression symptoms were assessed using the nine-item Patient Health Questionnaire (PHQ-9). The behavioral patterns were identified by the latent class analysis. The effects of behavioral patterns on the couple’s own depression symptoms (actor effect) and their partner’s depression symptoms (partner effect) were analyzed using the Actor-Partner Interdependence Model (APIM). Results Three behavioral patterns were identified: low-risk group, moderate-risk group, and high-risk group. The high risk of these behavior patterns would be associated with a higher score on the PHQ-9; for both husbands and wives, their behavioral patterns were positively associated with PHQ-9 scores (βhusband = 0.53, P < 0.01; βwife = 0.58, P < 0.01). Wives’ behavioral patterns were also positively associated with their husbands’ PHQ-9 scores (β = 0.14, P < 0.01), but husbands’ behavioral patterns were not associated with their wives’ PHQ-9 scores. Conclusions Wives’ depression symptoms were affected only by their own behavioral patterns, whereas husbands’ depression symptoms were influenced by both their own and their spouses’ behavioral patterns.